Rizaldy - Evasco, Eugene Y.; Doctor, Yasmin; Pacis, Carla M. (Quezon City LG & M Corp., 2011)
"An ordinary boy discovers heroism and greatness as he goes through a simple journey to know where his name came from. The simplicity is captured in charmimg but well-researched visuals that give the young reader a pleasant introduction to Jose Rizal.
Donated by Prof. Eugene Yambot Evasco.
PBBY Grand Prize 2011: Salanga Writer's Prize & Alcala Illustrators' Prize.
Keywords: Children's literature, English; Children's literature, Filipino